2021
DOI: 10.1002/cnr2.1527
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of assessment of progression in randomized oncology clinical trials

Abstract: Background: Progression in tumor assessments is often detected at a follow-up appointment rather than when actual change in progression has occurred, which can bias PFS outcomes.Aim: We sought to evaluate the frequency of tumor assessment scans in clinical trials of anti-cancer interventions and to compare this to recommended (National Comprehensive Cancer Network) and real-world frequencies of tumor assessments.Methods: In a cross-sectional analysis, we searched for articles published in the three top oncolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…We propose ORR as the surrogate endpoint for the interim analysis (dose optimization and preliminary efficacy evaluations) because it matures quicker (eg, two or three tumor assessments with median scan frequency of every 8 weeks 53 ) than time‐to‐event endpoints such as PFS and OS, and had been accepted in many cases for accelerated approvals depending on the context of use 29 . Slight modifications of the SDDO framework would allow the use of PFS for such decision‐making (especially, when PFS is a better predictor of OS than ORR).…”
Section: Discussionmentioning
confidence: 99%
“…We propose ORR as the surrogate endpoint for the interim analysis (dose optimization and preliminary efficacy evaluations) because it matures quicker (eg, two or three tumor assessments with median scan frequency of every 8 weeks 53 ) than time‐to‐event endpoints such as PFS and OS, and had been accepted in many cases for accelerated approvals depending on the context of use 29 . Slight modifications of the SDDO framework would allow the use of PFS for such decision‐making (especially, when PFS is a better predictor of OS than ORR).…”
Section: Discussionmentioning
confidence: 99%
“…In this example, simple reporting standardization of study follow-up, including in general practice, was found to be influential in outcome assessments, with a lack of systematic follow-up resulting in an underestimation of mortality [ 44 ]. Similarly, the frequency of assessment scans has been shown to be associated with higher median PFS for both treated and untreated populations [ 45 ]. As such, where assessments of PFS are made using real-world data with low or high frequency of assessments relative to the comparator data, the potential for bias may be high.…”
Section: Technical Challengesmentioning
confidence: 99%
“…Inclusion criteria for the systematic review were (1) articles published between January 1, 2010, and June 1, 2020, (2) articles written in the English language; and (3) original articles, brief reports, case reports, and research letters that reported primarily on cirAE management. Exclusion criteria included (1) articles published before 2010, (2) articles written in a language other than English, and (3) review articles, books, and editorials.…”
Section: Eligibility Criteriamentioning
confidence: 99%
“…We searched 4 major databases, including PubMed, Embase European, Web of Science, and Google Scholar, with selected key words 1 according to PRISMA guidelines (eFigure and eMethods in the Supplement). The search was performed on June 26, 2020.…”
Section: Eligibility Criteriamentioning
confidence: 99%
See 1 more Smart Citation